Ex ante analysis of the benefits of transgenic drought tolerance research on cereal crops in low-income countries - Kostandini, Genti; Mills, Bradford F.; Omamo, Steven Were; Wood, Stanley (Wiley, 2009)
This article develops a framework to examine the ex ante benefits of transgenic research on drought in eight low‐income countries, including the benefits to producers and consumers from farm income stabilization and the potential magnitude of private sector profits from intellectual property rights (IPRs). The framework employs country‐specific agroecological–drought risk zones and considers both yield increases and yield variance reductions when estimating producer and consumer benefits from research. Benefits from yield variance reductions are shown to be an important component of aggregate drought research benefits, representing 40% of total benefits across the eight countries. Further, estimated annual benefits of US$178 million to the private sector suggest that significant incentives exist for participation in transgenic drought tolerance research.